2020
DOI: 10.3389/fpls.2020.539460
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Loci and Candidate Genes Analyses for Tocopherol Concentration of Soybean Seed

Abstract: Tocopherol (Toc) occurs in soybean seeds and is extracted together with the soybean oil. Toc is utilized as an antioxidant in food and an additive in animal feed. A total of 180 representative accessions and 144 recombinant inbred lines (RILs) from the cross of ‘Hefeng 25’ and ‘OAC Bayfield’ were selected to evaluate individuals and total Toc concentrations in soybean seeds. The 180 soybean samples were sequenced by the approach of Specific Locus Amplified Fragment Sequencing (SLAF-seq). A total of 22,611 sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…For example, Yu et al (2019) utilized the RAD‐seq approach and identified candidate gene underlying the major QTL regulating flooding tolerance in soybean. Similarly, many other studies have demonstrated NGS‐based genotyping mediated candidate gene identification such as nitrogen fixation (Torkamaneh et al, 2020), plant height and primary branches in soybean (Borah et al, 2018), agronomic traits (Sonah et al, 2015), disease resistance (Zhao et al, 2015), and protein content (Sui et al, 2020). The NGS‐based WGRS has considerably increased the power of bulk segregant analysis (BSA) and its modified approaches and is being widely used in many plant species including soybean.…”
Section: Ngs‐based Genotyping: Gene Discovery and Mas In Soybeanmentioning
confidence: 91%
“…For example, Yu et al (2019) utilized the RAD‐seq approach and identified candidate gene underlying the major QTL regulating flooding tolerance in soybean. Similarly, many other studies have demonstrated NGS‐based genotyping mediated candidate gene identification such as nitrogen fixation (Torkamaneh et al, 2020), plant height and primary branches in soybean (Borah et al, 2018), agronomic traits (Sonah et al, 2015), disease resistance (Zhao et al, 2015), and protein content (Sui et al, 2020). The NGS‐based WGRS has considerably increased the power of bulk segregant analysis (BSA) and its modified approaches and is being widely used in many plant species including soybean.…”
Section: Ngs‐based Genotyping: Gene Discovery and Mas In Soybeanmentioning
confidence: 91%
“…Since altered tocopherol composition is of high interest for plant breeders, genetic loci associated with tocopherol composition control were mapped in most important oilseed crops including rapeseed, soybean, and sunflower ( Haddadi et al 2012 ; Wang et al 2012 ; Sui et al 2020 ). For sunflower, two major genes encoding MPBQ-MT and γ-TMT have been described, mutations in which may lead to altered tocopherol composition.…”
Section: Introductionmentioning
confidence: 99%
“…Tocopherols are present in relatively high concentrations in soybeans. In soybean and other oilseed crop species, tocopherol is extracted together with oil [16] and contributes significantly to the oil quality. Tocopherol composition is inherited as a quantitative trait and thus can be genetically dissected [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has seen the frequent application of the BSA-seq technique in soybean genetic and molecular studies, with a suite of candidate genes currently available for molecular breeding of the crop. However, many previous studies involving candidate gene detection focused on the use of mutant libraries and segregating populations [16,19], with only a few reported works that targeted variations present in natural mapping populations [22]. Additionally, several previous reports on candidate gene identification in the crop have been designed to target plant shoot architecture-related traits, with only minimal work conducted on nutritional composition attributes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation